Understanding Motivating Operations and the Impact on the Function of Behavior. (November 2020) - Hill, Doris Adams; Mantzoros, Theoni; Taylor, Jonté C.
Special educators are often considered the experts in their school when it comes to developing functional behavior assessments (FBA) and behavior intervention plans (BIP), yet rarely are they trained much beyond basic antecedents, behaviors, and consequences (ABC). This column discusses concepts that will expand special education professionals' knowledge to make better decisions regarding interventions for the students they serve. Specifically, the focus is on motivating operations (MO) and function-based interventions and the implications of these on behavior. Knowledge of the concept of MOs can enhance a teacher's ability to provide evidence-based interventions and more fully developed behavioral interventions for students in their purview.